Analysis of Sucrose Esters with Long Acyl Chain by Coupling of HPLC-ELSD with ESI-MS System - 朱金丽 汤艳峰 李建华 张淑芬 (Chinese journal of chemical engineering, 2009)
The analysis of sucrose esters with long acyl chain by improved high performance liquid chromatographic method with evaporative light scattering detection （HPLC-ELSD） and electrospray ionization mass spectrum （ESI-MS） is investigated. The improved HPLC-ELSD method for the separation and quantitation of commercial and synthesized sucrose esters is described. Samples are analyzed by means of a reversed-phase （RP） HPLC using a Hypersil C8 column （250 mm× 4.6 mm, 5 μm particle size） with methanol-tetrahydrofuran （vo）ume ratio of 90 ： 10） and water under gradientcondition as the mobile phase, in which the flow rate is 1.0 ml·min^-1 and the column temperature is set at 40℃. This procedure provides a complete separation and determination ot monoester, diester, triester and higher esters with different acyl chain lengths in each fraction by a single run, in combination with the ESI-MS technology. With this method, it is possible to determine the approximate compositions of monoto polyesters in one analysis and quantitate pure positional isomers precisely using an external standard method. It is found that the method of ESI-MS coupling with HPLC system for the analysis of sucrose esters is straight forward, rapid and inexpensive, and can be readily applied in synthesis, purification and structure studies.